Os determinantes da demanda de crédito bancário na modalidade de capital de giro para micro e pequenas empresas no Brasil - Soares, Jorge Luiz (Universidade do Vale do Rio dos Sinos, 2021)
This work aimed to identify the main determinants of the demand for bank credit in working capital modality for micro and small companies in Brazil. The study has a qualitative nature and an exploratory approach, using a theoretical literature review and a semi-structured qualitative interview, conducted with experts from financial system, with content analysis. The main results found indicate that the determinants of bank credit found in literature are also indicated by the respondents as being relevant for micro and small companies, with emphasis on the secondary interest rates, Selic and inflation, which have a negative relationship with credit demand in working capital modality by MSEs. Credit, GDP, operation duration and company size have a positive connection. In addition to identified indicators in literature, respondents made reference to three more determinants, with entrepreneurs’ consumption and confidence having a positive link with credit demand in working capital modality for MSEs, also entrepreneurs’ education or preparation were indicated by the respondents as having a negative connection.
Keywords: Demanda de crédito; Crédito bancário; Micro e pequenas empresas; Demanda de capital de giro; Credit demand; Bank credit; Micro and small companies; Working capital demand; ACCNPQ::Ciências Sociais Aplicadas::Administração